Empowering Women Entrepreneurs: Evaluating Access to Credit, Financial Literacy, Technical Know-How, and Government Support in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2025)
Background: Women’s entrepreneurship is closely linked to women’s empowerment and entrepreneurial development, both of which play a vital role in driving economic growth. Understanding the determinants of women’s entrepreneurial empowerment is particularly important in developing economies like Nepal, where women’s participation in business activities remains limited despite growing policy attention.Purpose: The main objective of this study is to evaluate the factors influencing women’s entrepreneurial empowerment in the Kathmandu Valley. The research seeks to identify key determinants and assess how entrepreneurial development contributes to women’s empowerment within the local context.Design/methodology/approach: An explanatory research design was adopted, focusing on women entrepreneurs in the Kathmandu Valley as the study population. A purposive sampling method was applied to collect data from 309 respondents. The study draws on the Resource-Based Theory and Entrepreneurship Theory to analyze influencing factors. Both descriptive and inferential analyses were conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM 4.0).Findings: The results show that most women entrepreneurs in Kathmandu are engaged in service-oriented businesses and often initiate their ventures without external credit but with strong family support. Major challenges identified include limited access to funding and difficulties balancing work and family responsibilities. The study highlights the need for targeted interventions such as training and education programs, improved financial access, mentorship opportunities, and networking initiatives. Furthermore, the findings indicate that women’s entrepreneurial development significantly influences women’s empowerment and mediates the relationship between technical know-how and empowerment.Conclusion: Women’s entrepreneurial development plays a crucial mediating role in enhancing women’s empowerment. Strengthening women’s access to resources, knowledge, and supportive networks can promote inclusive economic growth and sustainable entrepreneurship in Nepal.Keywords: Women Entrepreneurs; Resource-Based Theory; Smart PLS 4.0; Technical Know-How; Women Entrepreneurial Development